PENGARUH PEMBERIAN PUPUK KANDANG DAN PUPUK N, P, K TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN PADI DI LAHAN TADAH HUJAN - Afrikon Afrikon; Wardati Wardati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
This study aims to know the effect of combination and the main effect of giving manure and N,P,K fertilizer towards the growth and the production of rice plant and knowing the dosage of manure doses and N,P,K fertilizer on the growth and production of rice in rainfed land. This study was conducted in Binuang Village Bangkinang Sub-district Kampar Regency Riau Province. This study used a randomized block design (RBD) of 2 factors and 3 replications. The first factor was 3 levels of manure and the second factor was 4 levels of N, P, K fertilizer. The observation parameters consisted of plant height, maximum number of tillers, number of productive tillers, age out panicle, panicle length, number of grains per panicle, dry grain weight milled per plot andweighs 1,000 grains of grain. The combination of manure and N, P, K fertilizer  at 10 tons.ha-1 manure dosage with a dose of 138 kg N, 54 kgP2O5 , 60 kg K2O showed better results on the parameters ofthe maximum number of tillers, number of productive tillers, number of grain per panicle. The main factors of manure and N, P, K fertilizer showed better results on the parameters of the maximum number of tillers, number of productive tillers, age out panicle, panicle length, number of grain per panicle and dry grain weight milled per plot. Keywords : Rice plant, manure, N, P, K fertilizer, rainfed land